DICRANOLOMA (BRYOPHYTA: DICRANACEAE) DI TAMAN NASIONAL GUNUNG LEUSER (SUMATRA) - Fandri Sofiana Fastanti; Nunik Sri Ariyanti (Floribunda, 2017)
Fandri Sofiana Fastanti & Nunik Sri Ariyanti. 2017. The Dicranoloma (Bryophyta: Dicranaceae) of the Leuser Mountains National Park (Sumatra). Floribunda 5(6): 200–208. — The diversity of mosses of Leuser Mountains National Park is insufficienly reported, therefore this research was conducted in this national park to explore the diversity of Dicranoloma. This genus is easily recognized in the field by the long leaves and narrow costa. The diversity of Dicranoloma was observed based on the specimens collected in the national park, along trails at Gayo Luwes district from Rainforest Lodge Kedah to Angkasan summit (1417–2925 m asl). Ten species of Dicranoloma were identified, i.e. D. assimile, D. blumii, D. braunii, D. brevisetum, D. reflexum, D. daymannianum, Dicranoloma sp, D. dicarpum, D. eucamptodontoides and D. rugifolium. The last three species are new record for Sumatra while Dicranoloma sp. is still being identified. Key to the species, species descriptions, as well as  their distribution are provided.Keywords: Dicranaceae, Dicranoloma, Leuser Mountains National Park, mosses, Sumatra.Fandri Sofiana Fastanti & Nunik Sri Ariyanti. 2017. Dicranoloma (Bryophyta: Dicranaceae) di Taman Nasional Gunung Leuser (Sumatra). Floribunda 5(6): 200–208. — Keanekaragaman lumut sejati di Taman Nasional Gunung Leuser (TNGL) masih sedikit dilaporkan, sehingga penelitian ini dilakukan di taman nasional ini untuk mengeksplorasi keanekaragaman Dicranoloma. Marga ini mudah dikenali di lapangan berdasarkan daunnya yang panjang dan kostanya yang sempit. Keanekaragaman Dicranoloma diteliti berdasarkan spesimen yang dikoleksi dari taman nasional tersebut di sepanjang jalur pendakian Gayo Luwes dari Rainforest Lodge Kedah hingga puncak Angkasan (1417–2925 m dpl). Sepuluh jenis Dicranoloma telah diidentifikasi, yaitu D. assimile, D. blumii, D. braunii, D. brevisetum, D. reflexum, D. daymannianum, Dicranoloma sp, D. dicarpum, D. eucamptodontoides dan D. rugifolium. Tiga jenis terakhir merupakan  catatan baru bagi Sumatra, sedangkan Dicranoloma sp. masih dalam proses identifikasi. Kunci identifikasi, pertelaan dan persebaran jenis disediakan.Kata kunci: Dicranaceae, Dicranoloma, Taman Nasional Gunung Leuser, lumut sejati, Sumatra.